Communication and information needs of patients with cancer in Ghana: A scoping review - Kofi Gyasi Agyei; Ahmed-Rufai Yahaya; Natalie LeBlanc; Kah Poh Loh; Sally A. Norton (PLoS ONE, 2026)
Background Patients with serious illnesses, especially those with cancer, require information and good communication throughout their care. Effective communication is pivotal for quality cancer care, leading to improved quality of life, reduced anxiety, enhanced patient satisfaction, and adherence with treatment recommendations. Considering this, programs including serious illness conversation guides have been developed and implemented internationally (e.g., in the US) to improve communication skills in oncology care. Although many low- and middle-income countries are experiencing a growing cancer burden in both incidence and mortality, prognosis and treatment options are rarely discussed, which may be due to a lack of culturally sensitive guidelines in the African context. Notably, Ghana is facing a concerning increase in cancer prevalence and incidence. However, there is a paucity of information about the communication and information needs of patients with cancer in Ghana. This review will provide critical insights to guide the development or adaptation of culturally sensitive guidelines/frameworks appropriate for the Ghanaian context, with potential applicability to other African countries facing similar sociocultural and health system dynamics. Objective This scoping review sought to explore and synthesize existing evidence on the communication and information needs of patients with cancer in Ghana. Methods A systematic search was undertaken across PubMed, Web of Science, CINAHL, EMBASE, and PsycINFO databases using keywords and MeSH terms related to cancer, communication/information, and Ghana, employing Boolean operators “OR,” “AND.” The scoping review was guided by the five-stage methodological framework proposed by Arksey and O’Malley. The Preferred Reporting Items for Systematic reviews and Meta-Analyses extension for Scoping Reviews (PRISMA-ScR) was further adopted to ensure comprehensive reporting. Results Eight studies published between 2019 and 2023 met the inclusion criteria. Two major themes with sub-themes were identified including (1) information and communication experiences ((i) concealed information, (ii) disruption in communication, (iii) breaking bad news, (iv) power asymmetry-deference to healthcare providers), and (2) communication and information needs and expectations ((i) information on disease conditions, (ii) information on cancer treatment, (iii) information on prognosis, (iv) ongoing information, (v) involvement in decision-making). Conclusions Ghanaian patients with cancer strongly desire information regarding their condition and expect to be involved in decision-making. Despite patients with cancer’s desire for comprehensive information and shared decision-making, gaps in healthcare communication were evident, including limited accessibility to information, inadequate explanations by healthcare providers, and a lack of patient involvement in decision-making. Addressing these gaps requires tailored interventions to improve healthcare provider-patient communication.